Academic Information System In Higher Education : Applicating Delone and Mclean Model - Tahu, Gregorius Paulus; Yuesti, Anik (The journal of contemporary issues in business and government, 2021)
This Study uses descriptive analysis by using the Delone and McLean Model which is used to predict the success of academic information systems in several universities in Bali. By using a simple random sampling technique obtained a sample of some universities in Bali such as Universitas Mahasaraswati, Warmadewa and Dhyna Pura. The collection of data was conducted by questionnaires and interviews. Data analysis was done using Path Analysis with Structural Equation Modeling (SEM). The result shown that there is a positive relationship between the quality of the system with the use and satisfaction of users, a positive relationship between the quality of information with the use and satisfaction of users, a positive relationship between the quality of service with the use and satisfaction of users, a positive relationship between the use and satisfaction of users, a positive relationship between use and satisfaction users of net benefits. Thus, it can be concluded that all hypotheses are accepted